Does foreign direct investment and trade promote economic growth? Evidence from Albania - Sam Hobbs; Dimitrios Paparas; Mostafa E. AboElsoud (Economies, 2021)
Albania has experienced a rapid transition from a centrally planned economy to a mixed economy since the fall of communism in 1989. Policy changes, trade liberalization, and privatization have come about at a rapid pace, allowing foreign direct investment (FDI) and international trade to become key components of Albania's economy. Against this backdrop, this study investigates the relationships among FDI, trade, and economic growth in Albania. Annual time-series data were obtained from the World Bank. Then, the following econometric tests were performed on the variables representing FDI inflows, exports, and GDP as proxies for FDI, trade, and economic growth: the unit root test; the unit root test with a structural break; Johansen cointegration analysis; the error correction model; and the Granger causality test. The results revealed a long-term relationship between FDI, trade, and economic growth. The Granger causality tests found unidirectional causality. Economic growth brought about exports and FDI in the short term but not vice versa. In conclusion, policymakers need to design policies that promote technology-based, export-promoting FDI to meet the needs of the economy and develop specialized sectors that are competitive in the global market. Furthermore, the salient takeaway is that the penetration of export markets should be promoted as much as the furtherance of FDI.
Keywords: C22; E22; E61; 330; Albania; economic growth; FDI; foreign direct investment; GDP; trade